2014
DOI: 10.1590/0102-33062014abb3207
|View full text |Cite
|
Sign up to set email alerts
|

Conidial fungi from the semi-arid Caatinga biome of Brazil: The genus Menisporopsis

Abstract: The genus Menisporopsis S. Hughes is characterized by synnematous conidiomata around a central seta, phialidic conidiogenous cells and falcate to lunate 0-to 1-septate conidia with terminal setulae. Currently, nine species are included in the genus. In the course of investigating conidial fungi associated with decaying plant material in the semi--arid region of Brazil, we identified five

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Our observations of conidia in culture (15.5-19.5 × 2-3 µm with setulae 4.5-7.5 µm long) correspond to the conidia from nature in the protologue (15-18 × 2.4-3.1 µm with setulae 4.3-5.7 µm long) [9]. Cruz et al [70] reported specimens of A. novae-zelandiae on decaying leaves and petioles in Brazil with smaller conidia and shorter setulae (9.5-11 × 1-1.5 µm, setulae 3-5 µm long). Two of our Thailand strains (CBS 147509, CBS 147510), tentatively identified as A. novae-zelandiae, have longer conidia (18.5-23 × 2.5-3.5 µm) with longer setulae (6-10 µm) and correspond to the measurements given for this species by Matsushima [71].…”
Section: Phylogenetic Analysessupporting
confidence: 66%
See 1 more Smart Citation
“…Our observations of conidia in culture (15.5-19.5 × 2-3 µm with setulae 4.5-7.5 µm long) correspond to the conidia from nature in the protologue (15-18 × 2.4-3.1 µm with setulae 4.3-5.7 µm long) [9]. Cruz et al [70] reported specimens of A. novae-zelandiae on decaying leaves and petioles in Brazil with smaller conidia and shorter setulae (9.5-11 × 1-1.5 µm, setulae 3-5 µm long). Two of our Thailand strains (CBS 147509, CBS 147510), tentatively identified as A. novae-zelandiae, have longer conidia (18.5-23 × 2.5-3.5 µm) with longer setulae (6-10 µm) and correspond to the measurements given for this species by Matsushima [71].…”
Section: Phylogenetic Analysessupporting
confidence: 66%
“…CBS 694.74 and MUCL 43189 treated as separate species. Arcuatospora novae-zelandiae with shorter conidia from Brazil [70], for which DNA data are not available, probably represents another undescribed species based on morphology. Based on many published records, A. novae-zelandiae appears to be a common species with a widespread geographical distribution in subtropical and tropical regions.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Comments: as in the Brazilian material studied by Cruz et al (2014), our specimens have longer and wider setae than those reported by for the type material (Pirozynski & Hodges, 1973).…”
Section: Taxonomic Summarymentioning
confidence: 51%
“…Geographical distribution and substrate known: the type specimen of Menisporopsis profusa was detected on fallen leaves of Persea borbonia from South Carolina, USA (Pirozynski & Hodges, 1973). It has been collected in Malasya (Cybernome, 2017) and Brazil (Marques et al 2007;Cruz et al, 2014) on decaying leaves, stems and petioles.…”
Section: Taxonomic Summarymentioning
confidence: 99%
“…O gênero aeroaquático Helicosporium Nees (Webster & Descals 1981;Dix & Webster 1995;Tsui & Berbee 2006), por exemplo, já foi isolado de madeiras e folhas em ambiente terrestre no bioma Caatinga, por Cruz & Gusmão (2009a, b) e Cruz et al (2009). Esse grupo de fungos aeroaquáticos geralmente produz conídios com formas helicoidais (helicosporos), esporulando apenas quando o substrato é exposto ao ar (Webster & Descals 1981;Ando & Tubaki 1984;Alexopoulos 1996).…”
Section: Introductionunclassified